2020
DOI: 10.1113/ep088667
|View full text |Cite
|
Sign up to set email alerts
|

Lipid peroxidation in the descending thoracic aorta of rats deprived of REM sleep using the inverted flowerpot technique

Abstract: Oxidative stress-mediated lipid peroxidation is a known cause of endothelial injury or dysfunction. Deprivation of rapid eye movement (REM) sleep is associated with oxidative stress. To date, the pathogenesis of increased blood pressure after sleep deprivation remains poorly understood, particularly in the REM sleep phase. Our aim was to investigate the effects of REM sleep deprivation on blood vessels in the REM sleep-deprived rat model. Twenty-eight male Sprague-Dawley rats were divided into four equal group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 48 publications
0
15
0
1
Order By: Relevance
“…For adaptation, each rat in REMsd, REMsd-H and TC groups was adapted individually in a dry tank with two inverted flowerpots ( 25 26 ), while each rat in the control group was placed individually in a standard dry cage for 72 h. The size of the tank used was 30 cm height, 30 cm length and 60 cm width. For REMsd and REMsd-H groups, two flowerpots (6.5 cm diameter) were placed in the dry tank.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For adaptation, each rat in REMsd, REMsd-H and TC groups was adapted individually in a dry tank with two inverted flowerpots ( 25 26 ), while each rat in the control group was placed individually in a standard dry cage for 72 h. The size of the tank used was 30 cm height, 30 cm length and 60 cm width. For REMsd and REMsd-H groups, two flowerpots (6.5 cm diameter) were placed in the dry tank.…”
Section: Methodsmentioning
confidence: 99%
“…The water prevented the rats from sleeping and the rats would get back on the platform. The inverted flowerpot technique had been utilised by other studies to achieve REM sleep deprivation ( 25 28 ). Food and drinks were provided throughout the adaptation and experiment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sleep disorders related to inflammation and sympathetic activation lead to a change in blood vessel architecture, characterized by elastic fiber fracture and disorder, an increase in inflammatory cells, lipid peroxidation, inflammation, and sympathetic activation, which may induce endothelial dysfunction. Endothelial dysfunction is a critical factor in the increased risk of CVD [ 91 - 95 ]. In models of acute and chronic SD in healthy volunteers, Sauvet et al [ 96 , 97 ], Dettoni et al [ 98 ], measured biomarkers of microvascular reactivity and endothelial activation, elevated plasma E-selectin levels, and significantly increased sympathetic neural activity during SD.…”
Section: Mechanisms Of Chd Caused By Sdmentioning
confidence: 99%
“…Previous animal studies had shown the link between REM sleep deprivation and endothelial dysfunction, an early indicator of CVD development. [13][14][15] Endothelial dysfunction can be defined as the reduced vasodilatory capacity or any changes that impact the vasoprotective homeostatic function of the endothelium. 16 The dysfunction could be due to the damage to the vascular endothelium.…”
Section: Introductionmentioning
confidence: 99%